Building a Sustainable Yogyakarta Tourism Industry Through Muhammadiyah Business Ethics - Dani Yanuar Eka Putra (Jurnal Multidisiplin Indonesia, 2026)
Tourism growth in the Special Region of Yogyakarta in the 2020-2024 period has experienced a significant increase and contributed to the increase in the regional economy. However, these developments also raise various social and ecological problems. Such as inequality that gives birth to poverty, groundwater crisis, and an increase in the volume of waste. This article aims to analyze the relevance and application of Muhammadiyah's Islamic Business Ethics in building a sustainable tourism business in Yogyakarta. Using a descriptive-analytical approach based on literature studies, this study examines the principles of business ethics formulated by the Tarjih and Tajdid Council of Muhammadiyah, including at-Tauh?d, amanah, as-Sidq (honesty), al-'Adl (justice), al-Ib?hah (ability), at-Ta'?wun (Cooperation), al-maslahah (benefit), at-Tar?d? ( willingness), and Akhl?k al-Kar?mah. The results of the study show that these principles can be used as a normative foundation in tourism management that is not only profit-oriented. However, it also maintains ecological and social balance. The implementation of Muhammadiyah's business ethics in the tourism sector includes strengthening business responsibility and transparency, protecting the environment, involving local communities, providing halal and ethical tourism services, and strengthening the culture of honesty and trust in the entire tourism business chain. This research emphasizes that the application of Muhammadiyah's business ethics is able to become a strategic framework in building inclusive, equitable, and sustainable tourism in Yogyakarta.